Business management in the digital age: The power of electronic contracts - Neto, Abdo Dias da Silva; Silva, André Luis de Oliveira (Seven Editora, 2024)
The present study brings to light a focus directed to the uncertainties of information, one of the most complex issues in the new branch of Internet law. Its importance lies in the fact that, on the network, many of the facts and legal acts have international implications and, therefore, generate some problems that need urgent solution. These solutions are of interest to both the individual and the collective order, encompassing the interest of science as a set of knowledge in itself. The objective is to elucidate the unknown truth of the facts arising from electronic transactions, promoting a deeper and more comprehensive understanding of these interactions. In addition, it seeks to achieve a maturation of the current legal order, adapting it to the new realities imposed by technological and digital evolution. In this way, the study contributes to a more robust and effective legal scenario, capable of dealing with the contemporary challenges presented by the virtual environment. DOI:https://doi.org/10.56238/sevened2024.026-002